Rapid screening and determination of pesticides on lemon surfaces using the paper-spray mass spectrometry integrated via thermal desorption probe. (30th November 2021) - Chen, Kuan-Hong; Li, Yi-Chieh; Sheu, Fuu; Lin, Che-Hsin
Abstract: This paper presents a novel thermal desorption probe integrated with the corona-discharged assisted paper-spray mass spectrometry (PS-MS) for rapid detecting the residual pesticides on fruit surfaces. Pesticide detection can be simply achieved by scratching the fruit surface and then placed in front of the inlet of the MS for target pesticides screening. A novel ionization method comprising the electrospray ionization and the corona discharged is generated on the paper tip to simultaneously ionize the pesticide of high and low polarities for MS detection. Six pesticides composed of polar acetamiprid, azoxystobin, pyridaben and low polar chlorfenapyr, pyriproxyden, λ-cyhalothrin are successfully detected in seconds. The results are also validated with the LC-MS/MS and GC–MS/MS spectra performed via the standard protocols by a certificated laboratory of Eurofins Taiwan. The developed method provides a rapid, simple yet efficient way for screening residual pesticides on fruits.